MEKANISME INTERNAL CORPORATE GOVERNANCE DAN KINERJA INDUSTRI ASURANSI DI INDONESIA - Salam Fadillah Alzah (Jurnal Ekonomi Perusahaan, 2020)
This study looks at internal corporate governance mechanisms and performance of insurance companies listed or listed on the Indonesia Stock Exchange, where the dimensions of corporate governance are seen through the number of independent boards of commissioners, the board size, managerial ownership, board composition, and audit committee, and performance dimensions seen through the return on assets and Tobin'sQ. The method used is a literature review, reviewing related kinds of literature and analyzing problems through the concepts and results of previous studies. Previous studies have shown that corporate governance has a positive influence on Tobins' Q and ROA. Â  Keywords: insurance, the board of commissioners, managerial ownership, audit committee, return on asset, tobin'sQ